1998
DOI: 10.1159/000022441
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5’-Diphosphate-Induced Platelet Aggregation in Uremia Shows Resistance to Inhibition by the Novel Nitric Oxide Donor GEA 3175 but Not by S-Nitroso-N-Acetylpenicillamine

Abstract: Both bleeding and thrombosis are complications of uremia in patients on regular hemodialysis. An excessive endogenous formation of the vasodilator and platelet inhibitor nitric oxide (NO) has been proposed to contribute to the bleeding defect. Since exposure to pharmacological donors of NO, nitrovasodilators, can cause tolerance to NO, we investigated whether platelets from uremic patients on regular hemodialysis are influenced differently by NO donors than platelets from healthy subjects. A frequently used S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The compounds were equally potent and more potent than either 3-morpholinosydnonimine or S-nitroso-N-acetyl-D,Lpenicillamine (24). This effect could also be seen in platelets from uremic patients, although the response was significantly impaired (55). However, it has also been demonstrated that GEA 3175 alone does not prevent human platelet aggregation (15).…”
Section: Effects On Plateletsmentioning
confidence: 92%
“…The compounds were equally potent and more potent than either 3-morpholinosydnonimine or S-nitroso-N-acetyl-D,Lpenicillamine (24). This effect could also be seen in platelets from uremic patients, although the response was significantly impaired (55). However, it has also been demonstrated that GEA 3175 alone does not prevent human platelet aggregation (15).…”
Section: Effects On Plateletsmentioning
confidence: 92%